The Strategy Transforming purpose and Fundamental Management from The School of Meteorological, Climatological and Geophysical (STMKG) Agency Indonesia - Ita Soegiarto; Billy Tunas; Mahmuddin Yasin; Achmad Hidayat Sutawidjaya (International Review of Management and Marketing, 2019)
The research aims to explain the basic and objectives of the School of Meteorological, Climatological and Geophysical Agency which was originally the academy became college. Hopefully this change has a positive impact on organizational performance. The transforming the Academy of Meteorology and GEOPHYSICS (AMG) to the College of Meteorological Climatology and Geophysical (STMKG) is based on two factors. Internally, it can produce graduates who are reliable, trusted and recognized by the world and become the center of excellent for the education of Meteorological, Climatology and Geophysical (MKG). Externally, the change is based onThe rapid technological and community demands that the meteorological, climatological and geophysical agency (BMKG) is able to answer problems related to disaster is expected to minimized victims and disaster losses. This research uses qualitative methods with the case study approach, data collection using the purposive sampling technique since researchers want to get from various competent sources. The novelty of this research was conducted in the school of technical background that graduates are required to have the soul of socio entrepreneur, because it must provide information to the community in accordance with the jargon of BMKG namely fast, precise, accurate and understandable. The results showed that the changes that occurred resulted in a reliable graduate as a civil apparatus of the state placed throughout the task executing unit in the BMKG environment and provide MKG information in various areas such as Flight related weather info, high wave info, agricultural info planting time the most suitable and seismicity related to the potential of a tsunami.